Thoracic Kyphosis and Physical Function: The Framingham Study. Issue 10 (21st August 2017) - Lorbergs, Amanda L.; Murabito, Joanne M.; Jarraya, Mohamed; Guermazi, Ali; Allaire, Brett T.; Yang, Laiji; Kiel, Douglas P.; Cupples, L. Adrienne; Bouxsein, Mary L.; Travison, Thomas G.; Samelson, Elizabeth J.
Abstract : Objective: To evaluate the association between thoracic kyphosis and physical function. Design: Prospective cohort. Setting: Framingham, Massachusetts. Participants: Framingham Heart Study Offspring and Third Generation cohort members who had computed tomography (CT) performed between 2002 and 2005 and physical function assessed a mean 3.4 years later (N = 1, 100; mean age 61 ± 8, range 50–85). Measurements: Thoracic kyphosis (Cobb angle, T4‐T12) was measured in degrees using supine CT scout images. Participants were categorized according to Cobb angle to compare those in the highest quartile (Q4, most‐severe kyphosis) with those in the lowest quartiles (Q1‐Q3). Quick walking speed (m/s), chair‐stand time (seconds), grip strength (kg), and self‐reported impairments were assessed using standardized procedures. Analyses were adjusted for age, height, weight, smoking, follow‐up time, vertebral fractures, and prevalent spinal degeneration. Results: Thoracic kyphosis was not associated with physical function in women or men, and these results were consistent in those younger than 65 and those aged 65 and older. For example, walking speed was similar in adults younger than 65 with and without severe kyphosis (women, Q4: 1.38 m/s, Q1‐Q3: 1.40 m/s, P = .69; men, Q4: 1.65 m/s, Q1‐Q3: 1.60 m/s; P = .39). Conclusion: In healthy relatively high‐functioning women and men, kyphosis severity was not associated with subsequent physical function. Individuals at risk of functional decline cannot be targeted based on supine CT thoracic curvature measures alone.